Components of ICT competence of teachers of mathematics and informatics - Byrka, Marian (Information Technologies and Learning Tools, 2019)
Nowadays, the competency-based approach is becoming more and more traditional in Ukrainian education for every level – from preschool to postgraduate. Its focus is on two main concepts, “competency” and “competence”, interpreted in numerous ways in teaching and learning, which leads to inadequate educational results. Therefore, profound understanding and clear vision of the main concepts are very significant for the effective organization of the educational process. The article examines the ICT competency as a prerequisite for effective professional activities of pre-service teachers of mathematics and informatics in conditions of information society and digital world. The proper ICT competence level can considerably enhance both the teaching and learning processes, facilitate teachers’ professional development and their adaptation to changes in educational technologies. In this regard, defining the structure and content of ICT competency of pre-service teachers of mathematics and informatics is very important for clarification of educational process outcomes and students’ supporting personal characteristics needed to utilize ICT in their future job. The study introduces the conceptual model of structure of ICT competency and competence, which enlarges the focus of educational process to embrace value orientations and qualities of a person. In our opinion, the structure of ICT competency as well as of ICT competence should include the following criteria: knowledge, skills, habits, value orientations (motives, stimuli, values, interests and ambitions) and person’s qualities (abilities). Also, the article discusses the content of ICT competence of pre-service teachers of mathematics and informatics, based on the introduced model. ICT competence content data were acquired from empirical survey that involved students and practicing informatics teachers.
Keywords: competency-based approach, ICT competency, ICT competence, content of ICT competence, teachers of mathematics and informatics